2021
DOI: 10.1002/jbm.b.34952
|View full text |Cite
|
Sign up to set email alerts
|

Advances in electrospun scaffolds for meniscus tissue engineering and regeneration

Abstract: The meniscus plays a critical role in maintaining the homeostasis, biomechanics, and structural stability of the knee joint. Unfortunately, it is predisposed to damages either from sports-related trauma or age-related degeneration. The meniscus has an inherently limited capacity for tissue regeneration. Self-healing of injured adult menisci only occurs in the peripheral vascularized portion, while the spontaneous repair of the inner avascular region seems never happens. Repair, replacement, and regeneration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…4,45 Sufficient mechanical properties are a prerequisite for substitutes toward meniscus repair and regeneration. 27 Although many studies reported that bulk dmECM scaffolds had slightly decreased or even comparable compression strength with the native meniscus tissue, [50][51][52] they might be not optimal for implanting because of their dense matrix structure that does not allow cellular infiltration and poorly integrates with host tissue. 20,21 Previously, we reported a protocol to process dmECM into a formulation of injectable hydrogel, 8 which is compatible with cellular infiltration and integration with host tissue and has been widely exploited for meniscus repair in many preclinical investigations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,45 Sufficient mechanical properties are a prerequisite for substitutes toward meniscus repair and regeneration. 27 Although many studies reported that bulk dmECM scaffolds had slightly decreased or even comparable compression strength with the native meniscus tissue, [50][51][52] they might be not optimal for implanting because of their dense matrix structure that does not allow cellular infiltration and poorly integrates with host tissue. 20,21 Previously, we reported a protocol to process dmECM into a formulation of injectable hydrogel, 8 which is compatible with cellular infiltration and integration with host tissue and has been widely exploited for meniscus repair in many preclinical investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient mechanical properties are a prerequisite for substitutes toward meniscus repair and regeneration 27 . Although many studies reported that bulk dmECM scaffolds had slightly decreased or even comparable compression strength with the native meniscus tissue, 50–52 they might be not optimal for implanting because of their dense matrix structure that does not allow cellular infiltration and poorly integrates with host tissue 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a central feature that underlies the load bearing role of meniscus is the unique organization of collagen fibers, which is an essential requirement for a functional engineered meniscus. To this end, we, and other groups, have applied electrospinning (ES) to create nanofibrous scaffolds that emulate the meniscus collagen fibrillar matrix using natural and synthetic polymer (Grogan et al, 2020;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%